Hemorrhagic Cystitis and Possible Neurologic Disease from BK Virus Infection in a Patient with AIDS - Kinnaird, A. N. (Infection, 2010)
BK virus (BKV)-associated hemorrhagic cystitis occurs in bone marrow transplant recipients but is rare among other immunosuppressed patients. We present a rare case of BKVassociated hemorrhagic cystitis in a 48-year-old man with AIDS and previously diagnosed progressive multifocal leukoencephalopathy.